ChemInform Abstract: New Environment for a Two‐Dimensional Topological Insulator with Hexagonal Channels Hosting Diiodido‐Bismuthate(I) Anions in a Singlet State. Issue 16 (March 2016) - Rasche, Bertold; Van den Broek, Wouter; Ruck, Michael
Abstract: Bi38 Pt9 I14 (I) is obtained as the major product aside of minor amounts of Bi2 Pt by annealing mixtures of Bi, Pt, and BiI3 (290 °C, 1 week).